Elliptic Flow of Identified Particles in Pb–Pb Collisions at sNN=5.02 TeV - Er-Qin Wang; Yin-Qun Ma; Li-Na Gao; San-Hong Fan (Advances in High Energy Physics)
In this paper, by using a Tsallis-Pareto-type function and the multisource thermal model, the elliptic flow coefficients of particles π±, K±, p+p¯, Λ+Λ¯, and KS0 produced in Pb–Pb collisions at the center-of-mass energy of sNN=5.02TeV are investigated. In the process of collisional evolution, because of geometric structure, pressure gradient, and thermal diffusion effects, deformation and translation occurred in the isotropic emission source, leading to anisotropy in the azimuth distribution of the final-state particles. Based on these dynamic factors, the dependence of elliptic flow on transverse momentum is described as well.